2022
DOI: 10.1186/s12872-022-02550-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-vitamin K antagonist oral anticoagulants in venous thromboembolism patients: a meta-analysis of real-world studies

Abstract: Background The real-world studies on recurrent venous thromboembolism (VTE) and bleeding events of non-vitamin K antagonist oral anticoagulants (NOACs) in VTE patients have reported conflicting findings. Our study aimed to provide the direct comparison evidence of different NOACs for VTE patients in clinical practice settings. Methods Search of the medical literature was conducted using PubMed, Web of Science, EMBASE, Clinical Trials.gov, and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In summary, evidence from observational studies for DOAC treatment in acute VTE largely reflect findings of pivotal RCTs. In addition, two recent meta-analyses directly comparing different DOACs in patients with acute VTE have shown that apixaban had a significantly lower risk of major and minor bleeding events than rivaroxaban, with equivalent efficacy in prevention of recurrent VTE events [ 33 , 34 ].…”
Section: Risk Of Bleeding Complications Under Different Oral Anticoag...mentioning
confidence: 99%
“…In summary, evidence from observational studies for DOAC treatment in acute VTE largely reflect findings of pivotal RCTs. In addition, two recent meta-analyses directly comparing different DOACs in patients with acute VTE have shown that apixaban had a significantly lower risk of major and minor bleeding events than rivaroxaban, with equivalent efficacy in prevention of recurrent VTE events [ 33 , 34 ].…”
Section: Risk Of Bleeding Complications Under Different Oral Anticoag...mentioning
confidence: 99%
“…However, data that demonstrate therapeutic AC may not increase bleeding risk among those patients are increasingly emerging [ 2 , 44 ]. In a meta-analysis of real-world studies, 2 studies involving 923 patients showed no significant difference of major bleeding between dabigatran and rivaroxaban ( p = 0.25) [ 45 ]. Note that no significant association was found between platelet count or Child–Pugh Grade and major bleeding.…”
Section: Discussionmentioning
confidence: 99%